Transnational uncivil society networks: kleptocracy’s global fightback against liberal activism - Cooley, A; Heathershaw, J; Soares De Oliveira, R (SAGE Publications, 2023)
What is the global social context for the insertion of kleptocratic elites into the putatively liberal international order? Drawing on cases from our work on Eurasia and Africa, we sketch a concept of ‘transnational uncivil society’ which we contrast to ‘transnational activist networks’ (Keck and Sikkink, 1998). While the latter denotes the liberalising practices of global civil society, the former suggests a specific series of clientelistic relations across borders which open space for uncivil elites. This distinction animates a growing line of conflict in global politics. These kleptocrats eject liberal activists from their own territories and create new spaces to whitewash their own reputations and build their own transnational networks. To do so they hire political consultants and reputation managers, engage in public philanthropy, and forge new relationships with major global institutions. We show how these strategies of reputation-laundering are neither illicit nor marginal, but very much a product of the actors, institutions and markets generated by the liberal international order. We compare and contrast the scope and purpose of civil and uncivil society networks, we explore the increasing globalization of Eurasian and African elites as a concerted strategy to distance themselves from associations with their political oppression and kleptocracy in their home countries, and recast themselves as productive and respected cosmopolitans.